Clinical and metabolic factors associated with development and regression of nonalcoholic fatty liver disease in nonobese subjects. (24th January 2014) - Kim, Nam Hoon; Kim, Joo Hyung; Kim, Yoon Jung; Yoo, Hye Jin; Kim, Hee Young; Seo, Ji A; Kim, Nan Hee; Choi, Kyung Mook; Baik, Sei Hyun; Choi, Dong Seop; Kim, Sin Gon
Abstract Background & Aims The course of NAFLD (nonalcoholic fatty liver disease) and associated factors in nonobese subjects are not well established. We investigated contributing factors for the development and regression of NAFLD in nonobese Koreans, and whether they would differ from those of obese subjects. Methods Two thousand three hundred and seven adults aged over 18 years participated in this longitudinal observational study. The mean duration of follow‐up was 28.7 (±13.2) months. The participants were divided into two groups according to the baseline BMI (nonobese group: BMI <25 kg/m2, obese group: BMI ≥25 kg/m2). The presence or absence of NAFLD was assessed by abdominal ultrasonography. Results Body weight change was independently associated with both the development and regression of NAFLD in nonobese subjects as well as obese subjects. Among the subjects who developed NAFLD, the amount of weight change was higher in nonobese subjects compared to obese subjects (1.6 ± 3.9% vs 0.6 ± 4.2%, P = 0.022); and among those who showed regression of NAFLD, the amount of weight change was lower in nonobese subjects (−1.9 ± 4.0% vs −5.0 ± 4.6%, P < 0.001). Among all the components of metabolic syndrome, only high triglyceride levels (>150 mg/dl) at the baseline were significantly associated with both the development and regression of NAFLD in nonobese subjects (ORs, 1.54 (1.10–2.14), and 0.60 (0.38–0.96) respectively). Conclusion Body weight change and baseline triglyceride levels were strong indicators for the development and regression of NAFLD in a nonobese population.